Conditional Neutral Reward Promotes Cooperation in the Spatial Prisoner’s Dilemma Game - Tang, Yunxuan; Jing, Ming; Yu, Yong (Frontiers in Physics, 2021)
Reward is an effective mechanism that promotes cooperation. However, an individual usually reward her opponents in certain cases. Inspired by this, a conditional neutral reward mechanism has been introduced. In detail, an individual will reward his or her neighbors with the same strategy when the payoff of the focal one is higher than that of his or her neighbors. And simulations are conducted to investigate the impact of our mechanism on the evolution of cooperation. Interestingly, cooperation can survive and dominate the system. Nominal antisocial reward that defectors reward each other is rarely because of the greed of defectors. By contrast, cooperators inside the cooperative clusters share the payoff with cooperators on the boundary so that the latter can form shields to protect cooperators.